Structural Evolution of Perpendicular Lamellae in Diblock Copolymer Thin Films during Solvent Vapor Treatment Investigated by Grazing‐Incidence Small‐Angle X‐Ray Scattering. Issue 16 (11th July 2013) - Zhang, Jianqi; Posselt, Dorthe; Sepe, Alessandro; Shen, Xuhu; Perlich, Jan; Smilgies, Detlef‐M.; Papadakis, Christine M.
<x xml:space="preserve">Abstract</x> The structural evolution in poly(styrene‐b‐butadiene) (P(S‐b‐B)) diblock copolymer thin films during solvent vapor treatment is investigated in situ using time‐resolved grazing‐incidence small‐angle X‐ray scattering (GISAXS). Using incident angles above and below the polymer critical angle, structural changes near the film surface and in the entire film are distinguished. The swelling of the film is one‐dimensional along the normal of the substrate. During swelling, the initially perpendicular lamellae tilt within the film to be able to shrink. In contrast, at the film surface, the lamellae stay perpendicular, and eventually vanish at the expense of a thin PB wetting layer. During the subsequent drying, the perpendicular lamellae reappear at the surface, and finally, PS blocks protrude. By modeling, the time‐dependent height of the protrusions can be quantitatively extracted. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>